THE POTENTIAL OF THE GAME “MEANING DETECTIVE”: UNDERSTANDING OF MATHEMATICAL TERMS WITH HIGH SCHOOL STUDENTS (Interdisciplinary Studies Journal, 2025)
This research addresses the use of mathematical games as a trend in Mathematics Education, aiming to favor students' understanding of some mathematical terms. For this, a game was developed whose objective is to investigate the possible contributions of the game Detective of meanings, in the understanding of mathematical terms and questions for high school students. This study has a qualitative approach, which included two classes of the second year of high school in a public school in Petrolina-PE, totaling 74 students, being divided into two moments: in the first one, the game was experienced in the classroom and in the second moment, a verification questionnaire was applied, which allowed not only the analysis of data regarding the students' learning, but also made them realize the usefulness of the terms in mathematical questions. During the application of the game it was noticeable the motivation, interaction and curiosity of students to know if the definitions presented were correct. Finally, it is emphasized that there is didactic potential in the game Detective of meanings, given that it allows students to remember and learn new terms, allowing them to be active in the construction of knowledge.
Keywords: Mathematical terms; Mathematical Games; High school